مخطوط؛ رياض الأنس في علم الرقائق وسير أهل الحقائق لمؤلفه: عبد الرحمن بن محمد مخلوف أبو زيد الثعالبي الجزائري المالكيّ:دراسة وتحقيق - الطاهر عبد الرزاق الطاهر مسلم
Thanks to Allah and peaceful upon prophet of Allah, his family companions, it is well know that manuscripts form an important part of the heritage that created by Islamic civilization in all fields of human knowledge. These manuscripts are ignored and being forgotten as other types of our heritage only little are achieved. From this base, I chose science of (Raqaeq) for nourishing this science and adding book to Islamic libraries. All Muslims, either ignorant or learners, are in bad need to what soften their hearts and cause reverence to its god in time hearts, are in bad need to what soften their hearts and cause reverence to its God in time hearts became hard and cruel. I has chose Nafessa manuscript in this science with title of “written by Abo-laid Abd.al-Rahman ibn am mad ibn Makhloof Atthalibi AlJazaery Almalikey died in 875 a.h owner of the interpretation of Gawaher Alhesq It is large manuscript, included 164 chapters with 140 pictures. The author described this manuscript shortly saying that" I collect in my book autobiographies of good-men and worshipers and descriptions of favored and their sweet speech, that renew hearts, cure its hardness and assist in obeying its way, good willing. It also includes provisions, sermons, morals, stories, prophet's speeches, his followers, Imams and great scientists. We ask Allah forgiveness. Our work in achieving this manuscript after three copies was to indicate comprehensive study of the author's life and his age then achieving manuscript text, extracting texts stated by the author and attributing it to its source, responding on sayings that contradict with sharia with adding some correct speeches when we find weak texts. Through this book, we reached to the following summary: Thaalibi made this book variable with different subjects such as provisions chapters, juristic chapters, his excuse for that was to enter manner of facilitation and sermon in these chapters that soft one's heart. This manuscript contained 853 speeches including106 speeches agreed, 227 correct speech, 64 good speech, 26 stopped speech, 21 2weak speech, 15 denied speech, 154 created speech, 49 speech with no origin. As effects and news stated by the author in this manuscript, they are various and many including accepted easy ones, not true stories, this is an error return on this book. Not investigation in news and not distinguishing its correctness was one fault on this book and we commen5th on it in footnote. At the end of the search, there are seven indexes for facilitating skimming through the book.